Diagnosis of chest diseases using artificial immune system - Er, Orhan; Yumusak, Nejat; Temurtas, Feyzullah (Expert systems with applications, 2012)
► The study presents a comparative study for the realization of the chest diseases diagnosis. ► The best results were obtained using the artificial immune system. ► The artificial immune system classification accuracy is highly reliable for the chest diseases diagnosis. ► The artificial immune system is useful to help the expert while deciding the healthy and patient subjects. Chest diseases are one of the greatest health problems for people living in the developing world. Millions of people are diagnosed every year with a chest disease in the world. Chronic obstructive pulmonary, pneumonia, asthma, tuberculosis, lung cancer diseases are most important chest diseases and these are very common illnesses in Turkey. In this paper, a study on chest diseases diagnosis was realized by using artificial immune system. We obtained the classification accuracy with artificial immune system 93.84%. The result of the study was compared with the results of the previous similar studies reported focusing on chest diseases diagnosis. The chest diseases dataset were prepared from a chest diseases hospital’s database using patient’s epicrisis reports.